Interferensi Bahasa Ibu Terhadap Penguasaan Bahasa Indonesia Menulis Cerita Rakyak - ., Theopilus; Simega, Berthin; Baan, Anastasia (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The aim of this research is to describe the form of mother tongue that often interferes with mastery of Indonesian, as well as to find out the factors that cause mother tongue interference with mastery of Indonesian in writing the Mamasa folklore by class IX students of SMPN 2 Sesenapadang Mamasa. The type of research used is qualitative research. The research method used is direct observation (observation). The analysis techniques used are data collection, data redaction, data presentation and conclusions and withdrawal/verification. The results of the research show that it is true that there is interference in Mamasa's mother tongue with the mastery of Indonesian in writing Mamasa folk tales by class IX students of SMPN 2 Sesenapadang Mamasa, due to the students/speakers' daily habit of using their mother tongue.